How can entertainment influence children’s food choices towards healthy eating - Ettner, Doron (2014)
The purpose of this study is to explore whether the use of edutainment is able to positively influence children towards healthier eating habits. Using in-depth interview children’s food choices were compared pre and post exposure to educational action cartoon. The study focused on children form the age 5 to 10 in Israel, and was trying to assess at what age groups the message conveyed in the video was correctly retained. Parents were interviewed as well to validate the children’s answers about their food habits, as well as the children’s general media consumption. Results suggest that from age 7 children find the exposure engaging and the message is correctly retained in most cases, especially with the older children. We also noticed that most children were already doing healthy food choices before the exposure to the stimuli.